Effects of Kinesiotax Taping Over Posterior Neck Muscles on Pain and Functional Disability in patients with Mechanical Neck Pain - Maria Khan, Saima Riaz, Rehan Ramzan Khan, Huda Hamid, Zaigham Rasool Athar, Tausif Aamir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the effects of kinesiotax taping over posterior neck muscles on pain, functional disability and range of motion in patients with mechanical neck pain Methodology: A quasi experimental study was conducted on population aged between 30 to 40 years and 36 people were selected via Consecutive sampling technique. Study was conducted in Physiotherapy OPD, Services hospital, Lahore. Numeric Pain Rating Scale (NPRS) and Neck Disability Index (NDI) were used as outcome measure. Results: There was significant improvement in pain alleviation as pretreatment mean of NPRS was 6.55+0.33 and post treatment mean at 4 weeks was 3.88+0.21 while pretreatment mean of NDI was 42.33+2.92 and post treatment mean at 4 weeks was 15.05+1.56 in experimental group. Conclusion: The study concluded that kinesiotaping combined with stretching exercise program is more effective in decreasing pain and disability than stretching exercises alone in patients with mechanical neck pain.